New Evidence from Galeria da Cisterna (Almonda) and Gruta do Caldeirão on the Phasing of Central Portugal’s Early Neolithic - Zilhão, João (2021)
Funerary usage of Galeria da Cisterna (Almonda) and Gruta do Caldeirão began at the onset of the Neolithic and continued until Early Medieval times. At Cisterna, the thin Holocene deposit was unstratified; at Caldeirão, the stratigraphic sequence underwent post-depositional disturbance. Using radiocarbon dating, typological considerations, spatial distribution patterns, and physical anthropological data, these palimpsests can be disentangled to a significant extent. At both sites, the earliest depositions fall in the c. 5250–5500 cal BC interval and are associated with large numbers of beads. Wares extensively decorated with shell and comb impressions are likely to belong in this phase. Another style of decoration – shell impressions forming bands below the rim and garlands between prehension knobs – probably dates to a slightly later time. Burial continued at both sites through the c. 5000–5250 cal BC time range, but which decorative styles were then in fashion remains difficult to ascertain; it is likely that the irregular arrangements of shell impressions seen in some Cisterna vessels are among them. At Caldeirão, non-Cardial impressed and incised wares date to c. 4500–5000 cal BC, while undecorated wares are associated with human bone samples demonstrating two different periods of burial during the c. 3500–4000 cal BC interval. Most if not all of the nine Cardial individuals directly dated at the two sites died coevally with the more recent of the Mesolithic interments found in the shell-midden sites of the Tagus estuary.